CO2 reforming of methane combined with steam reforming or partial oxidation of methane to syngas over NdCoO3 perovskite-type mixed metal-oxide catalyst - Choudhary, Vasant R.; Mondal, Kartick C. (Applied Energy, 2006)
CO2 reforming with simultaneous steam reforming or partial oxidation of methane to syngas over NdCoO3 perovskite-type mixed metal oxide catalyst (prereduced by H-2) at different process conditions has been investigated. In the simultaneous CO2 and steam reforming, the conversion of methane and H2O and also the H-2/CO product ratio are strongly influenced by the CO2/H2O feed-ratio. In the simultaneous CO2 reforming and partial oxidation of methane, the conversion of methane and CO2, H-2 selectivity and the net heat of reaction are strongly influenced by the process parameters (viz. temperature, space velocity and relative concentration of O-2 in the feed). In both cases, no carbon deposition on the catalyst was observed. The reduced NdCoO3 perovskite-type mixed-oxide catalyst (Co dispersed on Nd2O3) is a highly promising catalyst for carbon-free CO2 reforming combined with steam reforming or partial oxidation of methane to syngas. (c) 2005 Published by Elsevier Ltd.
Keywords: Co/Nd2O3 catalyst; methane; NdCoO3 perovskite-type mixed metal-oxide catalyst; Oxy-CO2 reforming of methane; simultaneous CO2 and steam reforming of methane

Methane reforming over a high temperature stable-NiCoMgOx supported on zirconia-hafnia catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Chemical Engineering Journal, 2006)
The unusually high temperature stable NiCoMgOx (Ni/Co/Mg: 1:0.2:1.2)/zirconia-hafnia catalyst has been investigated for syngas generation via the catalytic partial oxidation of methane (CPOM), oxidative steam reforming of methane (OSRM) and oxidative CO2 reforming of methane (OCRM) processes. The catalyst, even when calcined at 1400 degrees C for 4 h, showed excellent activity/selectivity for the CPOM, OSRM and the OCRM reactions. On account of its high thermal stability, hot spots in the catalyst bed and/or high temperatures prevailing at the catalyst surface during the oxy-reforming processes would have little or no effect on the catalytic activity/selectivity of the NiCoMgOx/zirconia-hafnia catalyst, thus making the catalyst suitable even for operating under adiabatic conditions. While the selectivity for CO increased considerably with increasing reaction temperature for the CPOM process, the selectivity for H-2 was affected to a much lesser extent. The selectivity for CO and H-2 in the CPOM reaction was found to decrease with increasing space velocity; the H-2 selectivity was however affected to a greater extent. For the OSRM process, the H2O/CH4 ratio profoundly influenced the H-2/CO ratio and the heat of the reaction. Depending on the H2O/CH4 ratio, the OSRM process could be operated in a mildly exothermic, thermoneutral or mildly endothermic mode. The CO2 conversion increased rapidly with increasing OCRM temperature and correspondingly the exothermicity of the OCRM reaction was found to decrease with increasing reaction temperature. At 900 degrees C, the OCRM reaction was mildly exothermic and provided high methane conversion and syngas selectivity. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: high temperature stable catalyst; methane; oxy-dry reforming; oxy-steam reforming; Partial oxidation

Oxy-CO2 reforming of methane to syngas over CoOx/MgO/SA-5205 catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Fuel, 2006)
The OXY-CO2 methane reforming reaction (OCRM) has been investigated over CoOx supported on a MgO precoated highly macroporous silica-alumina catalyst carrier (SA-5205) at different reaction temperatures (700-900 degrees C), O-2/CH4 ratios (0.3-0.45) and space velocites (20,000-100,000cc/g/h). The reaction temperature had a profound influence on the OCRM performance over the CoO/MgO/SA-5205 catalyst; the methane conversion, CO2 conversion and H-2 selectivity increased while the H-2/CO ratio decreased markedly with increasing reaction temperature. While the O-2/CH4 ratio did not strongly affect the CH4 and CO2 conversion and H-2 selectivity, it had an intense influence on the H-2/CO ratio. The CH4 and CO2 conversion and the H-2 selectivity decreased while the H-2/CO increased with increasing space velocity. The O-2/CH4 ratio and the reaction temperature could be used to manipulate the heat of the reaction for the OCRM process. Depending on the O-2/CH4 ratio and temperature the OCRM process could be operated in a mildly exothermic, thermal neutral or mildly endothermic mode. The OCRM reaction became almost thermoneutral at an OCRM reaction temperature of 850 degrees C, O-2/CH4 ratio of 0.45 and space velocity of 46,000 cc/g/h. The CH4 conversion and H-2 selectivity over the CoO/MgO/SA-5205 catalyst corresponding to thermoneutral conditions were excellent: 95% and 97%, respectively with a H-2/CO ratio of 1.8. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: methane; oxy-CO2 reforming; Syngas

Partial oxidation of methane to syngas with or without simultaneous steam or CO2 reforming over a high-temperature stable-NiCoMgCeOx supported on zirconia-hafnia catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Applied Catalysis A-General, 2006)
A NiCoMgCeOx (Ni/Co/Mg/Ce: 1:0.2:1.2:1.2)/zirconia-hafnia catalyst with unusually high thermal stability has been investigated for syngas generation via a process that includes the catalytic partial oxidation of methane (CPOM), the oxidative steam reforming of methane (OSRM) and the oxidative CO2 reforming of methane (OCRM). The catalyst calcined at 1400 degrees C (for 4 h) showed excellent activity/selectivity for the CPOM, OSRM and the OCRM reactions; furthermore no catalyst deactivation was observed for a period of 20 h. For the CPOM process, the selectivity for H-2 was > 95% at reaction temperatures > 650 degrees C however temperatures above 800 degrees C were required to achieve > 95% CO selectivity. While the reaction temperature had a considerable influence on the CPOM product H-2/CO ratio, the space velocity (at 850 degrees C) did not affect it to any significant extent. For the OSRM process, the H2O/CH4 ratio and the reaction temperature had a strong effect on the product H-2/CO ratio and the heat of the reaction; depending on the H2O/CH4 ratio and reaction temperature, the OSRM process could be operated in a mildly exothermic, thermoneutral or mildly endothermic mode. The CO2 conversion was very strongly affected by the reaction temperature in the OCRM process; reasonably high CO2 conversion ( > 40%) could only be obtained at high OCRM reaction temperatures ( > 850 degrees C). The exothermicity of the OCRM reaction was found to decrease with increasing reaction temperature. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: dry (CO2) reforming; high-temperature stable; methane; oxy-steam reforming; Partial oxidation; Steam reforming; Syngas

Oxy-methane reforming over high temperature stable NiCoMgCeOx and NiCoMgOx supported on zirconia-haffnia catalysts: accelerated sulfur deactivation and regeneration - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Catalysis Communications, 2007)
NiCoMgOx and NiCoMgCeOx on commercial low surface area zirconia-haffnia catalysts have unusually high thermal stability (>= 2000 degrees C) for syngas generation via the methane partial oxidation process (J. Catal., 233, 36, 2005). Herein we report the results on accelerated sulfur deactivation (0.74 mol% sulfur in feed) and corresponding regeneration (at 800 degrees C in 1:1 O-2 + N-2 flow) over these catalysts. The NiCoMgCeOx catalyst, due to a larger mobility of lattice oxygen, showed a considerably higher resistance to sulfur poisoning; the higher mobility of the lattice oxygen in case of the NiCoMgCeOx catalyst may be related to the presence of CeO2. During the deactivation process, the selectivity for H-2 was decreased to a much greater extent than that for CO. Regeneration studies showed that even after complete deactivation of the catalysts, the original activity/selectivity of both the catalysts could be completely restored after a simple regeneration process. Based on their exceptionally high thermal stability, high activity/selectivity and easily regenerability, the NiCoMOx, and NiCoMgCeOx catalysts appear to be very promising candidates for the CPOM process. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Deactivation; high temperature stable; methane; Partial oxidation; Regeneration; Sulfur

Noble-metal-free heterojunction photocatalyst for selective CO2 reduction to methane upon induced strain relaxation - Das, Risov; Sarkar, Shreya; Kumar, Ritesh; Ramarao, Seethiraju D.; Cherevotan, Arjun; Jasil, Mohammed; Vinod, Chathakudath P.; Singh, Abhishek Kumar; Peter, Sebastian C. (ACS Catalysis, 2022)
Sunlight-driven CO2 hydrogenation has drawn tremendous attention. However, selective CH4 formation via CO2 photoreduction is very challenging. Herein, we report a metal oxide semiconductor heterojunction consisting of BiVO4 and WO3 as a photocatalyst for the efficient conversion of carbon dioxide (CO2) selectively to methane (105 mu mol g(-1) h(-1)) under visible light in the absence of a sacrificial agent. Wise selection of the reaction medium and the strategically tuned heterojunction upon strain relaxation suppresses the competitive hydrogen generation reaction. The detailed photophysical, photoelectrochemical, and X-ray absorption spectroscopy studies pointed to the Z-scheme mechanism of electron transfer, which favors superior electron and hole separation compared to the individual components of the composite catalyst and other well-known photocatalysts reported for CO2 reduction. The observations are further corroborated by experimental diffuse reflectance infrared Fourier transform spectroscopy and theoretical density-functional theory calculations, which reveal that the heterojunction has a lower free-energy barrier for CO2 conversion to CH4 due to the larger stabilization of the *CH2O intermediate on the strain-relaxed heterojunction surface, in comparison to the pristine BiVO4 surface. The present work provides fundamental insights for constructing high-performance heterojunction photocatalysts for the selective conversion of CO2 to desired chemicals and fuels.
Keywords: CO2 reduction; heterostructure; methane; Photocatalysis; Z-scheme

Binderless low silica X zeolite for methane separation from binary CO2/CH4 biogas stream: A comprehensive experimental and computational study - Yadav, Tushar R.; Shrotri, Aadesh R.; Kate, Pranjali N.; Devasia, George; Niphadkar, Prashant S.; Mali, Nilesh A.; Krishnamurty, Sailaja; Bokade, Vijay V.; Nandanwar, Sachin U. (Journal of Industrial and Engineering Chemistry, 2025)
This study presents the synthesis of binderless Na-LSX (B-Na-LSX) and binderless NaK-LSX (B-NaK-LSX). XRD, SEM, EDS, and N-2 physisorption were used for characterization of samples. Computational modelling of prepared sorbent was performed for the fundamental understanding of zeolite topology and adsorption behaviour. The breakthrough experiments are used to evaluate the adsorption capacities on CO2/CH4 (40/60 vol%) binary biogas stream. The results were compared with commercial Na-LSX (C-Na-LSX). The breakthrough adsorption capacity of B-Na-LSX was 3.08 mmol g(-1) and 0.29 mmol g(-1) of CO2 and CH4, respectively, at 300 K and 1 bar. CO2 sorption capacity of B-Na-LSX was similar to 11 % and similar to 17 % higher than B-NaK-LSX (2.77 mmol g(-1)) and C-Na-LSX (2.56 mmol g(-1)), respectively. DFT study reveals that the higher adsorption of CO2 over CH4 was attributed to higher charge transfer from CO2 to zeolite framework. Dual-bed six-step Pressure Swing Adsorption (PSA) was performed on B-Na-LSX at 6 bar. similar to 232 cycles were run with above 98 % of CH4 purity and similar to 74 % of recovery. The life-cycle test of sorbent was studied. It was implied that the designed sorbent is effective to produce the high purity of CH4 and can be utilized for a longer period for CH4 production.
Keywords: Binderless; Biogas; LSX zeolite; methane; PSA; Separation